Sphingosine 1-Phosphate to p38 Signaling via S1P1 Receptor and Gαi/o Evokes Augmentation of Capsaicin-Induced Ionic Currents in Mouse Sensory Neurons. (28th November 2014) - Langeslag, Michiel; Quarta, Serena; Leitner, Michael G; Kress, Michaela; Mair, Norbert
The perception of painful thermal stimuli by sensory neurons is largely mediated by TRPV1. Upon tissue injury or inflammation, S1P is secreted by thrombocytes as part of an inflammatory cocktail, which sensitizes nociceptive neurons towards thermal stimuli. S1P acts on G-protein coupled receptors that are expressed in sensory neurons and sensitize TRPV1 channels towards thermal stimuli. In this study, the S1P mediated signaling pathway required for sensitization of TRPV1 channels was explored. The capsaicin induced peak inward current (Icaps ) of sensory neurons was significantly increased after S1P stimulation within minutes after application. The potentiation of ICAPS resulted from activation of Gαi through G-protein coupled receptors for S1P. Consequently, Gαi led to a signaling cascade, involving phosphoinositide-3-kinase (PI3 K) and protein kinase C, which augmented ICAPS in nociceptive neurons. The S1P1 receptor agonist SEW2871 resulted in activation of the same signaling pathway and potentiation of ICAPS . Furthermore, the mitogen-activated protein kinase p38 was phosphorylated after S1P stimulation and inhibition of p38 signaling by SB203580 prevented the S1P-induced ICAPS potentiation. The current data suggest that S1P sensitized ICAPS through G-protein coupled S1P1 receptor activation of Gαi-PI3 K-PKC-p38 signaling pathway in sensory neurons.